Impacts of corn stover removal on carbon dioxide and nitrous oxide emissions. Issue 5 (29th August 2020) - Drury, C. F.; Woodley, A. L.; Reynolds, W. D.; Yang, X. M.; Phillips, L. A.; Rehmann, L.; Calder, W.
Abstract: Harvesting corn ( Zea mays L.) stover for production of biofuels, industrial sugars, bioproducts, and livestock bedding is increasing rapidly, but little is known of the impacts of stover removal on soil‐borne greenhouse gas (GHG) emissions. This study evaluated the impacts of removing surface corn stover (0, 25, 50, 75, 100 wt. % removal) on carbon dioxide (CO2 ) and nitrous oxide (N2 O) emissions from a sandy loam soil cropped to monoculture corn using conventional moldboard plow tillage (CT) and no‐tillage (NT). Stover removal systematically decreased CO2 emissions from CT, whereas stover removal had little effect on CO2 emissions from NT. In particular, the CT 0% stover removal treatment produced 47% greater CO2 emissions (5.75 Mg CO2 –C ha −1 ) than the CT 100% removal (3.91 Mg CO2 –C ha −1 ) treatment. Stover removal increased N2 O emissions from both tillage treatments, producing up to a 75% increase under CT (2.79 kg N ha −1 at 0% removal; 4.87 kg N ha −1 at 100% removal) and up to a 95% increase under NT (1.75 kg N ha −1 at 0% removal; 3.41 kg N ha −1 at 100% removal). Cumulative nitrate exposure increased in comparable patterns to N2 O emissions when stover residues were removed. There was a trade‐off in GHG emissions resulting from stover removal under CT, whereby increasing stover removal reduced CO2 emissions but increased N2 O emissions. In contrast, stover removal did not affect CO2 emissions under NT but it increased N2 O emissions especially at the 100% removal rates.